Основні етапи в історії розвитку українського правопису - Кортяк, Є. Ю. (ХНУРЕ, 2020)
Literacy is a very important element of any nation’s culture. Without writing, no nation could self-identify, evolve, or declare itself. Even the famous biblical phrase, "The Word was first..." reminds us that language, and therefore, writing, are very important for each of us. Spelling is a set of generally accepted and binding rules that set out the ways in which language can be transmitted in writing. Spelling covers punctuation too. As a rule, it develops historically, reflecting ancient traditions or new trends in the transmission of sounds, words, and forms that are found in each written language at different stages of its development. In this article we will look at these steps.
Keywords: правопис; українознавство